Muscle properties and coordination during voluntary movement - Herzog, W. (Journal of Sports Sciences, 2000)
The aims of this review were to provide some insight into the theoretical problems and questions associated with muscle coordination and control of movement, to consider some of the experimental findings on force-sharing among synergistic muscles, and to discuss some of the practical implications of force-sharing and movement control for optimal performance in sports. Theoretically, the distribution problem is introduced and the problems and difficulties of this approach in making quantitative predictions of force-sharing among muscles is discussed. Experimentally, the force-sharing research in the cat ankle extensor muscles is critically evaluated, and a complete force-sharing picture is given for the soleus and (medial) gastrocnemius for tasks covering a large range of speeds and intensities. In the application section, optimal performance criteria in jumping and cycling are considered. Furthermore, the plasticity of skeletal muscle properties is illustrated using examples from high-performance sports. The review ends with a summary of the topics discussed and suggestions for future research.